STUDI LITERATUR PENGARUH PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP SISWA INKLUSIF DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Nur Azzah, Harum Sari; Sekaringtyas, Tunjungsari; Wahyudiana, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inclusive education encourages the implementation of equitable and fair learning for all students, including those with special needs. In the context of Natural Science (IPA) subjects that require conceptual understanding and critical thinking skills, an adaptive and collaborative learning approach is needed. This article aims to examine the influence of the Jigsaw cooperative learning model on the activeness and learning outcomes of inclusive students in the upper grades of elementary schools. Using a literature study approach, an analysis of various previous studies was conducted. The results of the study indicate that the Jigsaw model is significantly able to increase learning engagement and understanding of science concepts of students, including those with special needs. These findings provide recommendations for teachers to implement cooperative learning strategies as part of inclusive educational practices.